A Team-Based Perspective for School Improvement: The Mediating Role of School Management Teams. Issue 2 (3rd April 2021) - Benoliel, Pascale
Abstract: The call for a more collective approach to school leadership motivated the present study. The proposed model examined the mediating role of school management team (SMT) effectiveness in the relationship of SMT characteristics of goal interdependence (the extent to which a shared goal requiring cooperation is present) and functional heterogeneity (the diversity of team member knowledge and skills) to school violence, academic emphasis and teacher absenteeism. Data were collected from a sample of 92 schools randomly selected from all state-secular and state-religious schools in Israel. A multi-source survey design from a sample of 92 SMTs, their principals, and teachers who are not SMT members was used. Data were aggregated at the school level of analysis. The results from structural equation model indicated that SMT effectiveness mediated the relationship of SMT goal interdependence to school violence, academic emphasis and teachers' absenteeism. SMT effectiveness facilitates the shift from more independent practices of teaching to teamwork, building leadership capacity promoting a positive and safely school learning environment. A work environment that promotes effective teamwork facilitating social relationships and knowledge exchange can provide a mechanism to create norms of teamwork that would benefit school effectiveness. The implications of these findings for both theory and practice are discussed.